2013
DOI: 10.14260/jemds/1672
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Stature From Hand Length and Length of Phalanges

Abstract: Stature or body height is one of the most important and useful anthropometric parameter that determine the physical identity of an individual. The study was done to estimate stature from the hand and length of phalanges. Study design: descriptive cross sectional study. Place of Study: department of Anatomy, Dr.S.N. Medical College, Jodhpur MATERIAL: One hundred males and one hundred females with the age of 18to 25yrs of, Dr.S.N. Medical College, Jodhpur. METHOD: Measurement of stature using standiometer and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 11 publications
3
20
0
1
Order By: Relevance
“…Agrawal J et al & Pal A et al have found nearly similar multiplication factor 8.835 and 9.05 respectively for hand length in males while Patel J et al found higher MF (9.32) for hand length in males in contrast to present study. 12,13,20 The regression equations derived to estimate stature from hand breadth in the present study for males was found to be HT=48.2061+(13.7460)*Avg. HB, while in females was HT=76.3169+(10.3399)*Avg.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Agrawal J et al & Pal A et al have found nearly similar multiplication factor 8.835 and 9.05 respectively for hand length in males while Patel J et al found higher MF (9.32) for hand length in males in contrast to present study. 12,13,20 The regression equations derived to estimate stature from hand breadth in the present study for males was found to be HT=48.2061+(13.7460)*Avg. HB, while in females was HT=76.3169+(10.3399)*Avg.…”
Section: Discussionmentioning
confidence: 58%
“…[10][11][12][13][14] Many recent studies have also shown a significant relationship between hand measurements with stature. [16][17][18][19][20] In the present study male to female ratio was 1:1, which was found to be similar to other studies by Dr. Sunil et al and Geetha et al 17,18 In the present study the mean stature of male subjects was found to be 163.54±5.217 cm, which was slightly lower than the findings of the other studies except Geetha et al (157.95±6.42 cm).…”
Section: Discussionmentioning
confidence: 99%
“…Tinggi badan diperoleh dengan mengukur jarak vertikal dari vertex ke lantai ketika kepala berada di posisi dataran Frankfurt dengan postur tegak tanpa alas kaki 3 . Titik medial paling dangkal di batas atas kondilus medial tibia sampai ujung malleolus medial 4 . Pengukuran dilakukan sebanyak tiga kali untuk menghindari kesalahan kemudian mencari rata-rata yang akan dicatat dan diolah pada tahap analisis data.…”
Section: Metodeunclassified
“…The newly collected data will be used for the development and design of a new firearm. It will be possible to use data also for other applications and evaluate the correlation between collected items [10].…”
Section: Anthropometry Database For Czech Populationmentioning
confidence: 99%